Population Pressure, Land Tenure, and Natural Resource Managemen - Keijiro Otsuka (Asian Development Bank Institute (ADBI), 2001)
Growing population has increased demand for land, trees, and water, which, coupled withtenure insecurity or the absence of clear property rights, has resulted in the over-exploitation ofnatural resources.The critical question is whether the current trend will continue and result in furtherdegradation of natural resources and, ultimately, the significant deterioration of human welfare.Based on the recently completed project concerning land tenure and the management ofland and trees in Asia and Africa (Otsuka and Place 2001), this paper attempts to identify the processby which population pressure leads to the individualization of land rights and its consequences on themanagement of land and trees.It is worth emphasizing that the individualization of land rights is a prerequisite fordesirable changes in farming systems.If unexploited forest land is open access and strong individualrights are granted on cleared land, excessive forest clearance takes place. This institutional rule isconsistent with the common rule of communal societies in which efforts to invest in land, includingforest clearance and tree planting, are rewarded by strong individual land rights. Interestingly,although women tend to inherit paddy land in areas where primarily females work for paddyproduction, men now tend to inherit rubber agroforests, in which primarily males work for rubber. Ifmen and women work equally, such as on cinnamon fields, egalitarian inheritance by daughters andsons has become common. Thus, the inheritance system seems to have evolved in such a manner as toprovide appropriate work incentives for men and women.
hdl:11540/4121
Keywords: 330